Demographic Factors, Self-efficacy on Financial Literacy in Upla - Suaebah, Ebah; Suciati, Fithri (KnE Social Sciences, 2022)
Financial literacy is the knowledge and ability of financial management that allows individuals to manage their finances more effectively. For managing finances, farmers in Indonesia still rely on informal financial institutions. There are several reasons for this – the farmers’ location being substantially far from the locations of financial institutions, their age and varied educational levels, and the level of confidence in achieving success in agriculture. This study, thus, identifies and analyzes the demographic factors and self-efficacy in financial literacy in upland horticultural crop farmers. The study population was upland horticultural plant farmers, the sampling technique was probability sampling, and the analysis was done using the two-way ANOVA technique. The results show a significant difference in the financial literacy between women and men. Although no difference was seen in the farmers’ financial literacy based on their age, a significant difference was noted based on their education. Additionally, a substantial difference was seen in the understanding based on self-efficacy. Keywords: demographic factors, self-efficacy, financial literacy